2005
DOI: 10.1007/s11218-005-1212-1
|View full text |Cite
|
Sign up to set email alerts
|

Grouping of Pupils in Secondary School Classrooms: Possible Links between Pedagogy and Learning

Abstract: Pupil groupings within classrooms are a constant social pedagogic factor which effect participation and learning. The grouping of pupils provides a dynamic relationship between learning tasks and the classroom context within which learning takes place. This paper explores types of pupil groupings found in secondary school classrooms related to themes of group size and composition, learning task, group interaction and teacher presence. The paper questions how classroom groupings may be related to the circumstan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…1. articulate, clarify and explain their thinking (Webb et al, 1995); 2. re-structure, clarify and in the process strengthen their own understanding and ideas to develop their awareness of what they know and what they do not know (Cooper, 1999;Howe et al, 1992); 3. adjust their explanations when presenting their thinking, which requires that they can also estimate others understandings (Baines & Howe, 2010); 4. listen to ideas and explanations from others -this may lead listeners to develop understanding in areas that are missing from their own knowledge (Kutnick et al, 2005); 5. elaborate and internalise their new understanding as they process the ideas they hear about from others (Damon, 1984;Wertsch & Stone, 1999); 6. actively engage in the construction of ideas and thinking as part of the co-construction of understandings and solutions (Coleman, 1998;Hatano & Inagaki, 1991;Hogan & Tudge, 1999;Webb & Palincsar, 1996); 7. resolve conflicts and respond to challenges by providing complex explanations, counter evidence and counter arguments (Baines et al, 2009;Howe & Tolmie, 1998;Mercer, 1995); 8. search for new information to resolve the internal cognitive conflict that arises from discrepancies in the conceptual understanding of others (Doise & Mugny, 1979;Howe, 2009). 9.…”
Section: Observing Collaborative Problem-solving Behavioursmentioning
confidence: 99%
“…1. articulate, clarify and explain their thinking (Webb et al, 1995); 2. re-structure, clarify and in the process strengthen their own understanding and ideas to develop their awareness of what they know and what they do not know (Cooper, 1999;Howe et al, 1992); 3. adjust their explanations when presenting their thinking, which requires that they can also estimate others understandings (Baines & Howe, 2010); 4. listen to ideas and explanations from others -this may lead listeners to develop understanding in areas that are missing from their own knowledge (Kutnick et al, 2005); 5. elaborate and internalise their new understanding as they process the ideas they hear about from others (Damon, 1984;Wertsch & Stone, 1999); 6. actively engage in the construction of ideas and thinking as part of the co-construction of understandings and solutions (Coleman, 1998;Hatano & Inagaki, 1991;Hogan & Tudge, 1999;Webb & Palincsar, 1996); 7. resolve conflicts and respond to challenges by providing complex explanations, counter evidence and counter arguments (Baines et al, 2009;Howe & Tolmie, 1998;Mercer, 1995); 8. search for new information to resolve the internal cognitive conflict that arises from discrepancies in the conceptual understanding of others (Doise & Mugny, 1979;Howe, 2009). 9.…”
Section: Observing Collaborative Problem-solving Behavioursmentioning
confidence: 99%
“…The prevalence of ability grouping by teachers in primary schools has been well documented (Barker Lunn, ; Hamilton & O’Hara, ; Marks, ), with the rationale for its use based on efforts to cater for diversity of learner needs (Petrilli, ; Hallam & Parsons, ). Critiques point to its ineffectiveness as a pedagogic tool, limiting the opportunity for all pupils (particularly those assigned to the lower‐ability groups) to engage in a broad and diverse curriculum as well as restricting the opportunity for peer engagement and learning (Slavin, ; Kutnick et al , ; ). Ability grouping is an act of symbolic violence (McGillicuddy & Devine, ), widening the gap of achievement between pupils (Lleras & Rangel, ; Schofield, ).…”
Section: Introductionmentioning
confidence: 99%
“…For Asian collectivists, the ideal grouping method would be based on affection and personal relationships. In fact, a number of studies on cooperative learning have found that friendship groups tend to have superior learning outcomes in comparison with random or ability groupings (Chauvet & Blatchford, 1993;Fraysse, 1994;Kutnick et al, 2005;Zajac & Hartup, 1997). However, very few studies have been done to confirm if friendship groups are really preferred and work better in Asian classrooms.…”
Section: Introductionmentioning
confidence: 99%